A dynamic approach to the relationship between inequality, social capital and institutions - Caramuta, Diego Martín (2005)
One of the main objectives of this paper is to show the dynamics that relates inequality, social capital and institutions. The most important result is that these dynamics could generate multiple equilibria. Thus, we can identify two types of equilibria: one with a low level of social capital and high level of inequality, supported by institutions created endogenously by the community; and on the other hand, an equilibrium with a high level of social capital, low inequality and institutions that favor social equality. The analysis made in this paper can be seen as a contribution to the literature on why a society may attain high levels of institutional development and social integration.